PENYULUHAN DAN DEMONSTRASI ALAT PENYIRAM TANAMAN OTOMATIS DENGAN TEKNOLOGI PERTANIAN PINTAR BAGI UMKM BIDANG PERTANIAN - Kiki Prawiroredjo; Engelin Shinta dewi Julian; Deiny Mardian W; Nora Azmi; Zulfikar (Jurnal Bakti Masyarakat Indonesia, 2023)
The Food and Agriculture Organization (FAO) predicts that by 2050 the world's population will reach 9.1 billion. That means agricultural production must increase by 70% in that year to meet the food needs of the population. Based on data from the official Cigelam village website, it is known that the number of farmers is 161 people or 2.34% of the total population of Cigelam village. Based on a field survey that was conducted in August 2022 in Cigelam village, there are smallholder farms that grow chili, corn and other fruit trees. Farmers water the plants at certain hours manually by turning on the water pump without seeing whether the plants are short of water or not. The problem faced by farmers/planters in Cigelam village is that they plant crops in areas with hot and temperate zones so that the plants need to pay more attention to soil moisture. This Community Service Program introduces smart agricultural technology or smart farming to farmers in the village of Cigelam which can increase the quality and quantity of agricultural products in a smart way. The implementation method used is to provide counseling about smart farming and demonstrations of automatic plant sprinklers based on soil moisture. From the answers to the evaluation of the implementation of the activities by the training participants it was found that the usefulness of the activities and the materials provided received good and very good scores of 92%. It is hoped that the benefits of this counseling can be spread again to other farmers and implemented. Food and Agriculture Organization (FAO)/Organisasi Pangan dan Pertanian memprediksi bahwa pada tahun 2050 jumlah penduduk dunia akan mencapai 9,1 milyar. Itu berarti produksi pertanian harus meningkat sebesar 70% pada tahun tersebut demi mencukupi kebutuhan pangan penduduk. Berdasarkan data dari website resmi desa Cigelam diketahui jumlah petani/pekebun adalah 161 orang atau 2,34% dari jumlah penduduk desa Cigelam. Berdasarkan survey di lapangan yang sudah dilakukan pada bulan Agustus 2022 di desa Cigelam terdapat pertanian rakyat yang menanam pohon cabai, jagung, maupun pohon buah-buahan lainnya. Petani menyiram tanaman mereka pada jam tertentu secara manual dengan menyalakan pompa air tanpa melihat apakah tanaman sedang kekurangan air atau tidak. Permasalahan yang dihadapi para petani/pekebun di desa Cigelam yaitu mereka menanam tanaman di daerah yang berzona panas dan sedang sehingga tanaman perlu lebih diperhatikan kelembaban tanahnya. Program Pengabdian kepada Masyarakat kali ini memperkenalkan teknologi pertanian pintar atau smart farming kepada para petani dan pekebun penduduk di desa Cigelam yang dapat meningkatkan kualitas dan kuantitas hasil pertanian secara pintar. Metode pelaksanaan yang digunakan adalah dengan memberikan penyuluhan tentang pertanian pintar dan demonstrasi alat penyiram tanaman otomatis berdasarkan kelembaban tanah. Dari jawaban evaluasi pelaksanaan kegiatan oleh peserta pelatihan diketahui bahwa kebermanfaatan kegiatan dan materi yang diberikan mendapat nilai baik dan sangat baik sebesar 92%. Dirahapkan manfaat dari penyuluhan ini dapat disebarkan lagi ke petani lain dan diimplementasikan.